COVID-19 and civil unrest undoing steady gains in karst conservation and herpetological research in Myanmar, and an impediment to progress - Quah, Evan Seng Huat; Grismer, Lee L.; Wood, Jr., Perry L.; Aung Lin; Myint Kyaw Thura (Wildlife Informaton Liaison Development Society, 2022)
The COVID-19 pandemic and political turmoil in Myanmar has dealt a severe blow to the country’s progress in herpetological research and the protection of limestone habitats. Both afflictions have reversed much of the scientific and conservation gains made in the past decade, and continue to hinder exploratory surveys and continued monitoring of threatened karst ecosystems. There is an urgent need to resume field studies and conservation efforts as soon as possible and continue enhancing the capacity of local scientific and technical staff in Myanmar.